2011
DOI: 10.1002/mnfr.201100128
|View full text |Cite
|
Sign up to set email alerts
|

Dicaffeoylquinic acids in Yerba mate (Ilex paraguariensis St. Hilaire) inhibit NF‐κB nucleus translocation in macrophages and induce apoptosis by activating caspases‐8 and ‐3 in human colon cancer cells

Abstract: The results suggest that diCQAs in Yerba mate could be potential anti-cancer agents and could mitigate other diseases also associated with inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 51 publications
3
45
4
3
Order By: Relevance
“…Caffeoylquinic acid derivatives inhibited LPS-induced Raw 264.7 macrophage inflammation by suppressing NO/iNOS and prostaglandin E2/cyclooxygenase-2 pathways through inhibiting nucleus translocation of NF-NB subunits, p50 and p65 (Puangpraphant et al, 2011). Tricaffeoylquinic acid seems to attenuate TNF-Į-stimulated inflammatory mediators production by keratinocytes, suppressing the activation of Akt and NF-țB pathways which may be mediated by reactive oxygen species, suggesting that this compound may exert inhibitory effects against the pro-inflammatory mediator-induced skin disease (Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Caffeoylquinic acid derivatives inhibited LPS-induced Raw 264.7 macrophage inflammation by suppressing NO/iNOS and prostaglandin E2/cyclooxygenase-2 pathways through inhibiting nucleus translocation of NF-NB subunits, p50 and p65 (Puangpraphant et al, 2011). Tricaffeoylquinic acid seems to attenuate TNF-Į-stimulated inflammatory mediators production by keratinocytes, suppressing the activation of Akt and NF-țB pathways which may be mediated by reactive oxygen species, suggesting that this compound may exert inhibitory effects against the pro-inflammatory mediator-induced skin disease (Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Nuclear factor kB (NF-kB) is a transcription factor and essential component link between inflammation and cancer. In innate immune pre-neoplastic and malignant cells, NF-kB upregulates inflammatory cytokines and enzymes including cyclooxygenase-2 (COX-2) and inducible nitric oxide (iNOS), which are an important factor for the synthesis of inflammatory mediators prostaglandin E2 (PGE2), anti-apoptosis, angiogenesis and metastasis (Puangpraphant, Berhow, Vermillion, Potts & Mejia, 2011). Puangpraphant et al (2011) demonstrated that 3,4-, 3,5-and 4,5diCQA fractions shown anti-inflammatory effect by suppressing the COX-2/PGE2 and iNOS/NO pathways.…”
Section: Colon Cancermentioning
confidence: 99%
“…The diCQA fractions inhibited RKO and HT-29 cell proliferation by inducing apoptosis rather than arresting cell cycle. Apoptosis occurs through induction of the ratio of Bax:Bcl-2 protein expression and diCQA induced the cleavage of procaspase-3 to active caspase-3, which is a key step of apoptosis (Puangpraphant et al, 2011 participating in these processes, which involve degradation of environmental barriers such as the extracellular matrix (ECM) and the basement membrane. Weng & Yen (2012) showed that CT26 cells treated with caffeic acid phenyl ester (CAPE) exhibited not only cell invasion inhibition, but also a decrease in matrix metalloproteinase (MMP)-2/-9 and vascular endothelial growth factor (VEGF) productions.…”
Section: Colon Cancermentioning
confidence: 99%
“…4 With such conflicting data, this review is very relevant and serves to advance our understanding of the association between maté drinking and the risk of oral and pharyngeal cancers.…”
mentioning
confidence: 99%